2020
DOI: 10.2147/ott.s248457
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA PTTG3P Sponge Absorbs microRNA-155-5P to Promote Metastasis of Colorectal Cancer</p>

Abstract: Objective: To study the role of LncRNA PTTG3P in colorectal cancer (CRC) and the underlying mechanism. Patients and Methods: The expression level of LncRNA PTTG3P was evaluated by quantitative real-time polymerase chain reaction (qRT-PCR) in CRC cell lines and tumor tissues from 43 CRC patients, and the correlations between LncRNA PTTG3P expression and the clinicopathological indicators and prognosis of CRC patients were analyzed. Then, a PTTG3P knockdown model in CRC cell lines HCT-8 and HCT-116 was construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…These results con rmed that PTTG3P overexpression serves as a valuable prognostic biomarker and aids innovatively e cient therapies for CRC patients. Additionally, our ndings stands in line with other research, Liu,et al [16] reported that PTTG3P was remarkably upregulated in CRC tumor samples than that in normal samples. Zhou, et al [17] revealed that PTTG3P is a valuable resource for identi cation in HCC progression and is useful for biomarker development.…”
Section: Discussionsupporting
confidence: 93%
“…These results con rmed that PTTG3P overexpression serves as a valuable prognostic biomarker and aids innovatively e cient therapies for CRC patients. Additionally, our ndings stands in line with other research, Liu,et al [16] reported that PTTG3P was remarkably upregulated in CRC tumor samples than that in normal samples. Zhou, et al [17] revealed that PTTG3P is a valuable resource for identi cation in HCC progression and is useful for biomarker development.…”
Section: Discussionsupporting
confidence: 93%
“…These results con rmed that PTTG3P serves as a valuable prognostic biomarker and aids innovatively e cient therapies for CRC patients. Additionally, our ndings stand in line with other research, Liu, et al [10] reported that PTTG3P was remarkably upregulated in CRC tumor samples than that in normal samples. Zhou, et al [11] revealed that PTTG3P is a valuable resource for identi cation in HCC progression and is useful for biomarker development.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, our findings stand in line with other research, Liu, et al [13] reported that PTTG3P was remarkably upregulated in CRC tumor samples than that in normal samples. Zhou, et al [14] revealed that PTTG3P is a valuable resource for identification in HCC progression and is useful for biomarker development.…”
Section: Discussionsupporting
confidence: 93%